Drivers of the growth–survival trade‐off in a tropical forest. (30th October 2019) - Meira‐Neto, João Augusto Alves; Nunes Cândido, Hélder Marcos; Miazaki, Ângela; Pontara, Vanessa; Bueno, Marcelo Leandro; Solar, Ricardo; Gastauer, Markus
Abstract: Questions: The growth–survival trade‐off is a central concept for the conflicting strategies of acquisitive species that grow quicker and conservative species that grow slower. Understanding which, and how, cross‐species functional traits contribute to the growth–survival trade‐off is a key topic for understanding the functioning of tropical forests. The present study aimed to: (a) determine if leaf traits, wood density and fruit size influence the growth–survival trade‐off at the community level; and (b) test the hypothesis that averaged leaf traits, averaged wood density and averaged fruit size among all trees of subplots explain tree height in a 50‐ha plot of secondary Atlantic Forest in Brazil. Methods: All trees with DBH > 3 cm had their heights estimated and were taxonomically identified. The functional traits used were leaf length (LL), leaf width (LW), petiole length (PL), petiole width (PW), leaf width/petiole width (LW/PW), leaf length × leaf width (LL*LW), wood density (WD), fruit length (FL) and fruit width (FW). Results: A total of 74, 335 trees of 178 species were recorded in 5, 076 subplots of 100 m 2 . Associations between functional traits and mean height ( H mean ) and height mode ( H mode ) were congruent with expected trends of LW, LL, LW/PW, WD and FW with the top‐ranked global model explaining most of the found variance suggesting that H mean and H mode are the best averaged response variables. The growth response represented by H mean and H mode had the most distinctive, congruent and consistent association with LW/PW, WD and FW. Conclusions: Higher LW and higher LW/PW indicated higher dependence of leaf blade on local microclimatic conditions, and lower dependence on petiole support for plant growth, which is beneficial for the acquisitive strategy. Smaller fruits and higher WD were also associated with the acquisitive strategy. Therefore, LW,  LW/PW, WD and FW influenced the growth–survival trade‐off at the community level and explained tree height variation in the studied tropical forest. Abstract : The growth–survival trade‐off is a central concept in plant ecology. The present study aimed to determine if leaf traits, wood density and fruit size influence the growth–survival trade‐off at the community level in a 50‐ha plot of secondary Atlantic Forest in Brazil. The overall growth response had the most consistent association with leaf width.